Contribution of impaired renal function to cardiovascular risk prediction models in renal transplant recipients. (25th October 2014) - Benguzzi, Mowad; Mansell, Holly; Hassan, Abubakar; Elmoselhi, Hamdi; Mainra, Rahul; Shoker, Ahmed
Abstract Background The Framingham risk score (FRS) and cardiovascular risk calculator for renal transplant recipients (CRCRTR‐MACE) quantify cardiovascular risk in renal transplant recipients (RTR). In contrast to the FRS, the CRCRTR‐MACE includes serum creatinine as a variable in the risk prediction equation. Objective To determine the influence of impaired renal function on performances of the two equations. Methods A chart review of 270 RTR transplanted from 1979 to 2012. High risk was defined at scores ≥20%. Standard statistical analyses included multivariate analysis (MVA), stepwise analysis, and odds ratio to estimate contributions of risk factors. Results Mean transplant duration was 9.51 ± 6.65 yr. Mean eGFR was 59.19 ± 28.26 mL/min/1.73 m2. FRS and CRCRTR‐MACE scores of least 20% were present in 9.3% and 24.8%, respectively, while 7.2% and 11.2% of RTR with eGFR ≥60 mL/min/1.73 m2 were high risk, respectively. Mean age, blood pressure, TC:HDL ratio, smoking, and diabetes were evenly distributed in patients with varying eGFR. FRS scores remained similar at wide eGFR range (≤30 mL/min/1.73 m2–≥90 mL/min/1.73 m2), while CRCRTR‐MACE scores significantly increased as eGFR decreased. Conclusions CRCRTR‐MACE identified more patients at high cardiovascular risk, even in those with more favorable renal function, suggesting a fundamental difference between the two calculators beyond renal function.